ON INTERRELATIONS BETWEEN GRADUONYMY AND ANTONYMY - Shirinova , Nilufar Djabbarovna (Innovative Development in Educational Activities, 2024)
The article deals with interrelations and differences between graduonymy and antonymy, which are two types of lexical-semantical relationships and it serves for the clearly understanding these two phenomena in the language system.